Transcriptome Profiling of Osteoblasts in a Medaka (Oryzias latipes) Osteoporosis Model Identifies Mmp13b as Crucial for Osteoclast Activation - Liu, Ranran; Imangali, Nurgul; Ethiraj, Lalith Prabha; Carney, Tom James; Winkler, Christoph (Frontiers in Cell and Developmental Biology, 2022)
Matrix metalloproteases (MMPs) play crucial roles in extracellular matrix (ECM) modulation during osteoclast-driven bone remodeling. In the present study, we used transcriptome profiling of bone cells in a medaka model for osteoporosis and bone regeneration to identify factors critical for bone remodeling and homeostasis. This identified mmp13b, which was strongly expressed in osteoblast progenitors and upregulated under osteoporotic conditions and during regeneration of bony fin rays. To characterize the role of mmp13b in bone remodeling, we generated medaka mmp13b mutants by CRISPR/Cas9. We found that mmp13b mutants form normal numbers of osteoblasts and osteoclasts. However, osteoclast activity was severely impaired under osteoporotic conditions. In mmp13b mutants and embryos treated with the MMP13 inhibitor CL-82198, unmineralized collagens and mineralized bone matrix failed to be degraded. In addition, the dynamic migratory behavior of activated osteoclasts was severely affected in mmp13b mutants. Expression analysis showed that maturation genes were downregulated in mmp13b deficient osteoclasts suggesting that they remain in an immature and non-activated state. We also found that fin regeneration was delayed in mmp13b mutants with a concomitant alteration of the ECM and reduced numbers of osteoblast progenitors in regenerating joint regions. Together, our findings suggest that osteoblast derived Mmp13b alters the bone ECM to allow the maturation and activation of osteoclasts during bone remodeling in a paracrine manner. Mmp13b-induced ECM alterations are also required to facilitate osteoblast progenitor recruitment and full regeneration of bony fin rays.